Chronic myeloid leukaemia patients at diagnosis and resistant to tyrosine kinase inhibitor therapy display exhausted T‐cell phenotype. (8th July 2022) - Harrington, Patrick; Dillon, Richard; Radia, Deepti; McLornan, Donal; Woodley, Claire; Asirvatham, Susan; Raj, Kavita; Curto‐Garcia, Natalia; Saunders, Jamie; Kordasti, Shahram; Harrison, Claire; de Lavallade, Hugues
Summary: The search for novel targets in chronic myeloid leukaemia (CML) is ongoing, to improve treatment efficacy in refractory disease and increase eligibility for tyrosine kinase inhibitor (TKI) discontinuation. Increased frequency of Tregs and effector Tregs was evident at diagnosis, together with increased expression of T‐cell exhaustion markers, including in regulatory T cells at diagnosis and in patients with refractory disease. Plasma analysis revealed significantly increased levels of cytokines including tumour necrosis factor (TNF)‐a and interleukin (IL)‐6 at diagnosis, in keeping with a pro‐inflammatory state prior to treatment. We hence demonstrate T‐cell exhaustion and a pro‐inflammatory state at diagnosis in CML, likely secondary to leukaemia‐associated antigenic overload associated with increased disease burden.